Sistem Pendukung Keputusan Penilaian Kinerja Mekanik Menggunakan Metode Analytic Network Process - Hutauruk, Jefri (Journal Global Technology Computer, 2024)
To produce good performance at PT Oriental Primasinergi Engineering, the company conducts an assessment of employees by assessing several criteria, namely initiative, security, discipline, cooperation, personal quality. The purpose of the employee assessment is carried out in order to produce good performance. The assessment of mechanical performance is carried out using the Analytic Network Process (ANP) method, weighting the criteria in ANP is assisted using SuperDecisions software with 5 criteria and 5 sub criteria using Microsoft Visual Studio 2008 for system design and MySQL as data storage. Each weight generated in ANP is used as a multiplier to assess the performance of mechanical employees at PT Oriental Primasinergi Enggineering. Calculation of performance assessment of mechanical employees assessed from 5 criteria get the results, namely fidaus: 0.21576, muslim pasaribu: 0.17634, supar dahrul: 0.25852, syafril: 0.16801, wira agri: 0,18138. The test results show that this system can solve problems in assessing the performance of mechanical employees, so that it can help in conducting employee performance appraisals.